Serum biochemical changes and growth response study following probiotic and phytobiotic supplementation in broiler chickens (Asian-Australasian Journal of Bioscience and Biotechnology, 2019)
Many alternative substances have been investigated for their potential to replace antibiotics as growth promoters. Probiotics and phytobiotics are some of the products that can be used as growth promoters in broiler. The present study was designed to investigate either single or combined effect of a probiotic and phytobiotic on serum bio-chemistry and growth performances in broilers. A total of 50 Cobb-500 day old chicks were divided into five groups (10 birds each). The birds of Group A were offered a basal diet (corn-soya based), Group B basal diet + 0.10% Renamycin 100®, Group C basal diet + 0.15% probiotic (Bio-Top®), Group D basal diet + 0.10% phytobiotic (Galibiotic) and Group E basal diet + 0.15% Bio-Top® + 0.10% Galibiotic. Body weight, feed intake, weight gain, feed conversion ratio (FCR) and serum bio-chemistry (Triglyceride, cholesterol, LDL, HDL, ALT, AST, creatinine) were recorded. Serum biochemical values differed significantly (P